A Creeping Transformation? - Bauer, Michael W. author. aut Link
XIII, 193 p.
Keywords: How can we approach the Commission's role as co-manager of policy implementation? Why should we expect the Commission to be pulled into domestic policy execution and to accumulate something like an implementation management capacity? How should we conceptualise the Commission's linkage with post-decision management issues? Finally, how does the Commission's involvement in the application of EU policies, if any, significantly change everything? Such questions are answered in this study, which is concerned with what may be called the implementation management capacity of the European Commission. Simply put, this is the role the Commission plays in the implementation of large-scale European spending programmes. While it is true that the Commission's predominant prerogatives are to draft legislation and facilitate bargaining, it also has a role in post-decision policy management. This role is of increasing importance for the emerging governance of the European Union. Readership: social scientists, journalists and all those interested in the role of the European Commission in shaping EU policies.